Physiological basis and differentially expressed genes in the salt tolerance mechanism of Thalassia hemprichii - Shen, Jie; Wu, Zhongjie; Yin, Lei; Chen, Shiquan; Cai, Zefu; Geng, Xiaoxiao; Wang, Daoru (Frontiers in Plant Science, 2022)
Seagrass plays a vital role in the stability of marine ecology. The human development of marine resources has greatly affected the survival of seagrass. Seawater salinity is one of the important factors affecting its survival. Seagrass can survive in high saline environments for a long time and have evolved a variety of effective tolerance mechanisms. However, little is known about the molecular mechanisms underlying salinity tolerance by seagrass. Thalassia hemprichii is a seagrass species with a global distribution. It is also an ecologically important plant species in coastal waters. However, the continuous environmental deterioration has reduced the ecological niche of seagrasses gradually. This study showed that the optimal salinity for T. hemprichii is 25 to 35 PSU. Although it can survive under high and low salinity, high mortality rates are common in such environments. Further analyses revealed that high salinity induces growth and developmental retardation in T. hemprichii and further causes yellowing. The parenchyma cells in T. hemprichii also collapse, the structure changes, soluble sugar accumulates rapidly, soluble proteins accumulate rapidly, the malondialdehyde (MDA) content reduces, and lipid peroxidation reduces in plant membranes. The molecular mechanisms of salt tolerance differ significantly between marine and terrestrial plants. We found 319 obtained differentially expressed genes (DEGs). These genes regulate transport and metabolism, promoting environmental adaptation. The expression of these genes changed rapidly upon exposure of T. hemprichii to salinity stress for three hours. This is the first report on the physiological and biochemical changes and gene expression regulation of T. hemprichii under different salinity conditions. The findings of this study deepen our understanding of T. hemprichii adaptations to changes in the shoal living environment.